ASEAN Economic Bulletin. (ISEAS, 1984)
Published articles, short papers, and reviews on the economics and political economy of the ASEAN (Association of Southeast Asian Nations) and as member countries. It also provides documentation on ASEAN economic development and cooperation and on research activities in relation to the Asia-Pacific region.